Amelioration of visual deficits and visual system pathology after mild TBI with the cannabinoid type-2 receptor inverse agonist SMM-189. (May 2019) - Guley, Natalie M.; Del Mar, Nobel A.; Ragsdale, Tyler; Li, Chunyan; Perry, Aaron M.; Moore, Bob M.; Honig, Marcia G.; Reiner, Anton
Abstract: Mild TBI is often accompanied by visual system dysfunction and injury, which is at least partly caused by microglial neuroinflammatory processes initiated by the injury. Using our focal cranial blast mouse model of closed-skull mild TBI, we evaluated the ability of the cannabinoid type-2 (CB2) receptor inverse agonist SMM-189, which biases microglia from the harmful M1 state to the beneficial M2 state, to mitigate visual system dysfunction and injury after TBI. Male C57BL/6 or Thy1-EYFP reporter mice received a closed-head blast of either 0-psi (sham) or 50-psi to the left side of the cranium. Blast mice received vehicle or 6 mg/kg SMM-189 daily beginning 2 h after blast. Sham mice received vehicle. In some mice, retina and optic nerve/tract were assessed morphologically at 3–7 days after blast, while other mice were assessed functionally by Optomotry 30 days after blast and morphologically at ≥30 days after blast. Mice sacrificed at 3–7 days were treated daily until sacrificed, while those assessed ≥30 days after blast were treated daily for 2 weeks post blast. Axon damage was evident in the left optic nerve and its continuation as the right optic tract at 3 days post blast in vehicle-treated blast mice in the form of swollen axon bulbs, and was accompanied by a significant increase in the abundance of microglia. Testing at 30 days post blast revealed that the contrast sensitivity function was significantly reduced in both eyes in vehicle-treated blast mice compared to vehicle-treated sham blast mice, and axon counts at ≥30 days after blast revealed a ∼10% loss in left optic nerve in vehicle-treated blast mice. Left optic nerve axon loss was highly correlated with the left eye deficit in contrast sensitivity. Immunolabeling at 30 days post blast showed a significant increase in the abundance of microglia in the retinas of both eyes and in GFAP + Müller cell processes traversing the inner plexiform layer in the left eye of vehicle-treated blast mice. SMM-189 treatment reduced axon injury and microglial abundance at 3 days, and mitigated axon loss, contrast sensitivity deficits, microglial abundance, and Müller cell GFAP upregulation at ≥30 days after blast injury. Analysis of right optic tract microglia at 3 days post blast for M1 versus M2 markers revealed that SMM-189 biased microglia toward the M2 state, with this action of SMM-189 being linked to reduced axonal injury. Taken together, our results show that focal left side cranial blast resulted in impaired contrast sensitivity and retinal pathology bilaterally and optic nerve loss ipsilaterally. The novel cannabinoid drug SMM-189 significantly mitigated the functional deficit and the associated pathologies. Our findings suggest the value of combatting visual system injury after TBI by using CB2 inverse agonists such as SMM-189, which appear to target microglia and bias them away from the pro-inflammatory M1 state, toward the protective M2 state. Highlights: Focal cranial blast traumatic brain injury in mouse visual deficits. Focal cranial blast TBI causes optic nerve axon loss and retinal pathology. Focal cranial blast TBI activate retinal and optic nerve microglia to the M1 state. The cannabinoid type-2 inverse agonist SMM-189 ameliorates TBI visual system harm. SMM-189 benefit after TBI is associated with biasing of microglia to the M2 state.